Disarmament and Military Cooperation as Vectors of National Security Ensuring - Ekaterina Sergeevna Andreeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article investigates a study of disarmament as a principle of contemporary international law. An analysis of the international legal doctrine and existing international and domestic acts of states leads the author to the conclusion that in modern international law the principle of disarmament has not formed yet. It can be proved only about the formation of the principle of arms control, which is closely connected with one of the principles of international humanitarian law - the principle oflimitation of means and methods of warfare. At the same time disarmament is essential for the maintenance of international peace and security. On the other hand, the military cooperation of the states in accordance with the principles of international law is an important element for national, regional and universal security.